2001
DOI: 10.1002/bdd.259
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary disposition of valproic acid during prolonged intravenous infusion: contributions of unbound clearance and protein binding

Abstract: Circadian variations in disposition have been observed for a variety of agents, including anticonvulsants. Valproic acid (VPA), an anticonvulsant used to control generalized and partial seizures, has exhibited diurnal oscillations in steady-state concentrations during long-term administration to humans and non-human primates. The present study was conducted to assess potential diurnal changes in the disposition of VPA during prolonged i.v. infusion in rats. Animals, maintained on a strict 12-h per day light cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1008 mg/kg per day), 42 mg/kg/h was administered to the intermittent group. A previous study by Arens and Pollack 31 showed sustained therapeutic plasma levels by hourly continuous infusion of 42 mg/kg of VPA. The longer time between the administration of VPA doses (e.g.…”
Section: ( ) T D $ F I G ]mentioning
confidence: 85%
See 1 more Smart Citation
“…1008 mg/kg per day), 42 mg/kg/h was administered to the intermittent group. A previous study by Arens and Pollack 31 showed sustained therapeutic plasma levels by hourly continuous infusion of 42 mg/kg of VPA. The longer time between the administration of VPA doses (e.g.…”
Section: ( ) T D $ F I G ]mentioning
confidence: 85%
“…and was found to produce therapeutic serum levels of VPA (600-1800 mmol/L). 31 Drug delivery was carried out via an EEG/infusion cable (made in house) connected through an EEG and fluid swivel, allowing free movement, to a 32 channel video-EEG system (Compumedics Limited, Melbourne, Australia) and a multisyringe programmable pump (KDS 230, Walker Scientific, Wangara, Australia) as previously described. 28 To assist in preventing infusion lines clotting, animals were given a daily 0.1 mL bolus of heparinised saline (20 IU/mL).…”
Section: Drug Deliverymentioning
confidence: 99%
“…All rats (n = 17) were given heparinised saline as described above for 3 days and on the 4 th day rats were weighed and assigned randomly to either 42 mg.kg −1 .hr −1 valproate (Sigma, USA) (n = 9) a dose that is known to suppress seizures [38], [40] or saline (n = 8). After 5 days of treatment (day 8) rats were euthanized with an overdose of sodium pentobarbital (1 ml/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Animals in the chronic infusion experiment (n = 38) first received saline (0.9% NaCl) for 4-5 days, at a rate of 1 ml/h followed by two infusion periods (3-5 days each) of 42 mg/kg valproate (Sigma, USA) (Arens and Pollack, 2001) (1 ml/h) separated by two days of saline (0.9% NaCl, 1 ml/h) (Table 1). Infusion solutions contained 4 IU/ml of heparin to prevent blood clotting.…”
Section: Drug Infusion and Veeg Recordingsmentioning
confidence: 99%